Efficacy of plasmapheresis and semi‐selective immunoadsorption for removal of anti‐HLA antibodies. Issue 3 (30th November 2020) - Jambon, Frédéric; Merville, Pierre; Guidicelli, Gwendaline; Taton, Benjamin; De Précigout, Valérie; Couzi, Lionel; Moreau, Karine; Visentin, Jonathan
Abstract: Background: In organ transplantation, apheresis is frequently used for removal of anti‐HLA antibodies. However, it is unclear whether plasmapheresis (PP) or semi‐selective immunoadsorption (IA) should be employed, and the optimal number of apheresis sessions required to reach post‐treatment objectives is also unknown. Methods: We enrolled 43 patients from Bordeaux University Hospital who were treated with PP (n = 29) or IA (n = 14) for antibody‐mediated rejection or pre‐transplant desensitization. Using Luminex single‐antigen flow beads, we assessed the initial mean fluorescence intensity (MFI) of 1416 positive beads with MFIs obtained after 7 to 8 apheresis sessions (extended protocol) and, if a serum was available, after the first four sessions (short protocol). Results: MFI reduction after extended apheresis protocol was stronger with IA [87% (61%‐100%)] than with PP [73% (22%‐100%)] ( P < .001). Indeed, 59% of the beads had a final MFI < 2000 with IA, whereas only 38% with PP ( P < .001). The efficacy of removal depended on initial MFI but not on HLA specificity. A short protocol of apheresis showed excellent results without superiority of IA over PP for antibodies with an initial MFI < 3000. For antibodies showing MFI ≥2000 after four sessions, the residual MFI predicted the effectiveness of four additional sessions. Conclusion: Monitoring the MFI of anti‐HLA antibodies before and during apheresis protocol can guide physicians in the selection of apheresis technique and the number of sessions to be performed.